Verdant Eden / Nurul Fatin Syamimi Mat Rozi ... [et al.] - Mat Rozi, Nurul Fatin Syamimi; Shukor, Zarifah Zawanah; Md.Zaki, Nur Zaim Faizzi; Misnat, Nordin (2024)
Verdant Eden Space Design is a unique space design that combines nature, recreation, and modernity, offering a peaceful retreat within the university park. The park features architectural elements that evoke natural forms, fostering a seamless integration between built environments and the natural world. Elevated pathways and dynamic structures with solar panels to generate power, adorned with vertical gardens and climbing plants, this space invites visitors to explore and interact with their surroundings. Eco-friendly walkways with footsteps generate power meander through the park, offering varying perspectives and encouraging discovery. The sculptural canopy, with its organic shape providing shelter and shade, enhances the park's tranquil ambience. The park also features recreational elements like a rock-climbing wall and a skate bowl, blending relaxation with activity. These features cater to a wide range of activities, from quiet contemplation to physical exercise. Verdant Eden Space's design exemplifies how urban spaces can be transformed into multifaceted environments that promote healing, well-being, environmental awareness, and community engagement. It serves as a model of thoughtful design that enhances design student life and urban living, providing a vital green space that fosters a deeper connection to nature and offers a respite from the urban hustle toward sustainable space design.